On optimal emission control: Taxes, substitution and business cycles. - Jussi Lintunen; Lauri Vilmi (Bank of Finland, 2013)
This paper studies the cyclical properties of optimal emission taxes and emissions using a real business cycle model with a stock pollutant. We derive conditions for the procyclicality of optimal emission tax and show that the tax is in typical conditions procyclical. The possibility of a countercyclical behavior of the emission tax increases if 1) the pollution is short-lived and the emission transfer into environmental damages rapidly 2) emissions are countercyclical, 3) marginal damages are strongly increasing and 4), in disutility case, the marginal utility of consumption increases with the increase in the intensity of the harmful environmental process. In the climate change context we show that the optimal carbon tax is procyclical irrespectively on the production technology. Instead, the technology is a key determinant of the cyclicality of the emissions. The optimal carbon tax correlates almost fully with the consumption and as a rule-of thumb, it could be indexed to the consumption level of the economy. The relative scale of tax deviations relative to the consumption deviations is determined by the inverse of the intertemporal elasticity of substitution. Comparison between the optimal emission tax and an optimally set constant emission tax shows that the constant tax leads to very slightly higher emissions but the general economic effects are next to negligible.
URN:NBN:fi:bof-20140807498
Keywords: E32; Q54; Q58; 330; optimal emission tax; cyclical properties